Analysis of Fable Character Value Contained In 2nd Grade Theme 7 Books - Muslimah (LADU: Journal of Languages and Education, 2023)
Background:  This research is motivated by the problem of the importance of instilling character values ​​from an early age to grade 2 elementary school students. The title of this study was taken because the researcher wanted to identify the content of character values ​​in the text of fables contained in thematic books on the theme of 7th grade 2 SD based on the Guidelines for Implementation of Character Education as an effort to build student development in education applied by the Ministry of Education and Culture (2011). Purpose: This study was to identify the content of character values ​​in the text of fables contained in thematic books on the theme of 7th grade 2 SD based on the Guidelines for Implementation of Character Education. Design and methods: This study used a qualitative research method with a content analysis research design. The source of the data used is the thematic book of the 7th grade class 2 SD theme. The instrument used is based on the indicators contained in the Guidelines for Implementation of Character Education implemented by the Ministry of Education and Culture (2011). Results: The results of this study indicate that the fables contained in the thematic books on the 7th grade of 2nd grade elementary school contain character values ​​in accordance with the Ministry of Education and Culture's Guidelines for Implementation of Character Education (2011). The character values ​​found are honest, discipline, hard work, curiosity, friendly/communicative, peace-loving, social care, and responsibility. There are ten-character values ​​that are not contained in the 7th grade 2 SD theme book, namely religious character values, tolerance, creative, independent, democratic, national spirit, love for the motherland, respect for achievement, love to read, care for the environment. Of the 8-character values ​​found in the fairy tale book, there are 2 most dominant character values, namely the character values ​​of hard work and love of peace. Then in the suitability analysis that the character values ​​contained in the fables are in accordance with the thematic books on the 7th grade class 2 elementary school theme.